2011
DOI: 10.1111/j.1530-0277.2011.01515.x
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol and Maternal Uterine Vascular Adaptations During Pregnancy-Part I: Effects of Chronic In Vitro Binge-Like Alcohol on Uterine Endothelial Nitric Oxide System and Function

Abstract: Background Pregnancy-induced utero-placental growth, angiogenic remodeling, and enhanced vasodilation are all partly regulated by estradiol-17β-mediated activation of endothelial nitric oxide synthase (eNOS) and nitric oxide (NO) production. However, very little is known about the effects of alcohol on these maternal utero-placental vascular adaptations during pregnancy and its potential role in the pathogenesis of Fetal Alcohol Spectrum Disorders (FASD). In this study, we hypothesized that in vitro chronic bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
6

Relationship

5
1

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 71 publications
2
29
0
Order By: Relevance
“…A study in pregnant C57BL/6 J mice demonstrated that NO modulation of the systemic mesenteric artery vascular response was hampered due to alcohol exposure (Cook et al 2001). In vitro studies have shown that binge-like alcohol exposure impairs eNOS activation and reduces mRNA levels for angiogenic genes and related proteome in endothelial cells of the ovine uterine artery, hence blunting the uterine vascular adaptations, including vasodilatory and angiogenic pathways (Ramadoss et al 2010, 2011; Ramadoss and Magness 2011, 2012a, b, d). Finally, these findings have significant implications on fetal growth and development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A study in pregnant C57BL/6 J mice demonstrated that NO modulation of the systemic mesenteric artery vascular response was hampered due to alcohol exposure (Cook et al 2001). In vitro studies have shown that binge-like alcohol exposure impairs eNOS activation and reduces mRNA levels for angiogenic genes and related proteome in endothelial cells of the ovine uterine artery, hence blunting the uterine vascular adaptations, including vasodilatory and angiogenic pathways (Ramadoss et al 2010, 2011; Ramadoss and Magness 2011, 2012a, b, d). Finally, these findings have significant implications on fetal growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the impact of maternal alcohol exposure on uterine perfusion has received minimal attention and there is a paucity of information in the literature. An earlier study in sheep has shown that acute alcohol exposure leads to a significant reduction in uterine blood flow (Falconer 1990) and a series of in vitro studies have shown that binge-like alcohol exposure alters utero-placental vascular adaptations (Ramadoss et al 2011, 2012; Ramadoss and Magness 2011, 2012a, b; Subramanian et al 2014). However, to our knowledge, so far no study has been conducted to investigate the effect of repeated binge alcohol exposure during pregnancy on uterine blood flow.…”
Section: Introductionmentioning
confidence: 99%
“…In a chick extraembryonic model, moderate and heavy alcohol doses (30% or 50%, 24 or 48 h) impaired vascular development, and the authors (89) have attributed these deficits to angiogenic growth factors, associated receptors, and oxidative stress, whereas Gu et al (29), again using the chick extraembryonic model, showed that administration of alcohol (0.25 g·kg Ϫ1 ·day Ϫ1 , 7 days) induced greater branching of blood vessels (29). In uterine artery endothelial cells derived from pregnant ewes, in vitro chronic binge-like alcohol exposure (300 or 600 mg/dl) inhibits estradiol 17␤-induced endothelial proliferation (67). In a more recent study, biotinylated capture and color-coded reporter probes were used to digitally characterize 85 angiogenesisassociated genes in the uterine vasculature following chronic binge alcohol exposure (22,26).…”
Section: Maternal Alcohol Effects On Reproductive Vasculaturementioning
confidence: 94%
“…In one study, alcohol administered in the diet (GD 6 -18, peak BAC, 0.11 g/dl) to pregnant C57BL/6J mice showed reduced NO modulation of the mesenteric artery vascular response (14). In vitro chronic binge-like alcohol treatment (300 and 600 mg/dl) to uterine artery endothelial cells derived from third trimester pregnant ewes decreased excitatory serine-635 endothelial NO synthase phosphorylation levels at both concentrations (67). In placental villi, in vitro acute alcohol exposure for 2 h (100 and 200 mM) decreased tissue NO concentrations and cGMP levels and increased superoxide dismutase activity (39).…”
Section: Effects Of Alcohol On Maternal Endocrine and Paracrine Systementioning
confidence: 96%
“…We and others have reported that alcohol consumption during pregnancy results in altered uterine endothelial adaptations (Ramadoss, Jobe, & Magness, 2011; Ramadoss & Magness, 2011, 2012a, 2012c), agonist-dependent vessel relaxation (Subramanian et al, 2014), spiral artery remodeling (Gundogan et al, 2008), and blood flow (Falconer, 1990). However, there exists no study on alcohol-related myogenic response, a critical gestational uterine vascular adaptation.…”
Section: Introductionmentioning
confidence: 99%